2006
DOI: 10.1677/joe.1.06483
|View full text |Cite
|
Sign up to set email alerts
|

The expression of atrial natriuretic peptide in the oviduct and its functions in pig spermatozoa

Abstract: Locally synthesized atrial natriuretic peptide (ANP) and its receptors have been found in reproductive tissues of various mammals, and play an important role in the acrosome reaction of human sperm. The objective of the present study was to examine the expression of ANP and its receptors in pig spermatozoa and oviduct, and the effect of ANP on pig spermatozoa function. The expression of ANP and its receptors was analyzed by RT-PCR. Only natriuretic peptide receptors-A (NPRA) mRNA was detected in fresh sperm. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 58 publications
0
21
0
1
Order By: Relevance
“…Its receptor was detected in spermatozoa (Zhang et al 2006). The preincubation of boar spermatozoa with atrial natriuretic peptide has been shown to induce the acrosome reaction (Zhang et al 2006).…”
Section: Atrial Natriuretic Peptidementioning
confidence: 99%
See 1 more Smart Citation
“…Its receptor was detected in spermatozoa (Zhang et al 2006). The preincubation of boar spermatozoa with atrial natriuretic peptide has been shown to induce the acrosome reaction (Zhang et al 2006).…”
Section: Atrial Natriuretic Peptidementioning
confidence: 99%
“…It has been shown that pre-incubation of spermatozoa with this peptide increased the oocyte penetration rate and decreased the polyspermy rate and the average number of sperm per penetrated oocyte in pigs (Zhang et al 2006). …”
Section: Atrial Natriuretic Peptidementioning
confidence: 99%
“…The merging of follicular fluid and the oviductal fluid after ovulation may provide sufficient chemoattractants to ensure the arrival of sperm at the ampulla. Atrial natriuretic peptide (ANP) and its precursor A (NPPA) are found in pig, mouse, rat and rabbit oviducts (Kim et al 1997, Zhang et al 2006, Bian et al 2012. ANP receptor (NPR1), however, is expressed on the sperm.…”
Section: Chemotaxismentioning
confidence: 99%
“…ANP receptor (NPR1), however, is expressed on the sperm. Upon ANP and NPR1 binding, ANP activates the cyclic GMPdependent protein kinase pathway (PKG) and induces acrosome reactions in pig, cow and human sperm (Zamir et al 1995, Rotem et al 1998, Zhang et al 2006. This reaction might provide additional evidence regarding the role of ANP as a human sperm chemoattractant (Zamir et al 1993, Anderson et al 1995.…”
Section: Chemotaxismentioning
confidence: 99%
“…Moreover, some oviductal proteins have been shown to interact with gametes and to improve efficiency of IVF in porcine (McCauley et al 2003, bovine (Martus et al 1998), human (O' Day-Bowman et al 1996), and equine (Mugnier et al 2009) species. Some of these proteins, such as osteopontin, have been identified (Hao et al 2006, Goncalves et al 2008, Monaco et al 2009) in cattle and pigs and atrial natriuretic peptide A (Anderson et al 1994, Zamir et al 1995, Zhang et al 2006 and oviductin (oviduct-specific glycoprotein; Martus et al 1998, Buhi 2002, McCauley et al 2003 in cattle, pigs, and humans.…”
Section: Introductionmentioning
confidence: 99%